Going Dark: How Google and Facebook Fought the Australian News Media and Digital Platforms Mandatory Bargaining Code - Leaver, Tama (M/C - Media and Culture, 2021)
The first two months of 2021 saw Google and Facebook ‘go dark’ in terms of news content on the Australia versions of their platforms. In January, Google ran a so-called “experiment” which removed or demoted current news in the search results available to a segment of Australian users. While Google was only darkened for some, in February news on Facebook went completely dark, with the company banning all news content and news sharing for users within Australian. Both of these instances of going dark occurred because of the imminent threat these platforms faced from the News Media Bargaining Code legislation that was due to be finalised by the Australian parliament.